Pendidikan Teologi Ahlus Sunnah Wal Jamaah: Konsep, Klasifikasi, dan Implementasi dalam Kehidupan Muslim - Rabi’ah Nurman Maulidya; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the education of Ahlus Sunnah Wal Jamaah theology, focusing on its concept, classification, and implementation in Muslim life. Using a literature review method, this research explores primary Islamic sources, such as classical theological books, along with modern academic references that explain the 20 Attributes (Sifat 20) in Ahlus Sunnah Wal Jamaah doctrine. The analysis is conducted descriptively and critically to understand how this theology is taught and applied in various aspects of life. The findings reveal that theological education plays a crucial role in shaping Muslim beliefs and character while maintaining relevance in the Islamic education system. This study also recommends more effective teaching strategies for comprehending and internalizing Ahlus Sunnah Wal Jamaah theology.